2003
DOI: 10.2223/jped.934
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination in HIV infected children: immunologic and viral load changes

Abstract: ResumoObjetivo: verificar se a vacinação contra influenza em crianças infectadas pelo HIV aumentaria a carga viral e reduziria os linfócitos T CD4+, conseqüentes à ativação da imunidade com antígenos dependentes do linfócito T.Métodos: estudo prospectivo descritivo, com 51 crianças infectadas pelo HIV, vacinadas contra influenza em 1999, em Florianó-polis, Brasil. Coletaram-se amostras de sangue no dia da vacinação, 14 a 20 e 60 a 90 dias após, para determinação dos níveis da carga viral do HIV e de linfócitos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The mean CD4 count after 6 months had increased back towards the baseline. A similar transient dip in CD4 count was seen in a prospective observational study among 51 HIV‐positive children in Rio De Janeiro after receiving seasonal influenza vaccine . Some of our study participants experienced viral ‘blips’ post‐vaccination.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The mean CD4 count after 6 months had increased back towards the baseline. A similar transient dip in CD4 count was seen in a prospective observational study among 51 HIV‐positive children in Rio De Janeiro after receiving seasonal influenza vaccine . Some of our study participants experienced viral ‘blips’ post‐vaccination.…”
Section: Discussionsupporting
confidence: 83%
“…A similar transient dip in CD4 count was seen in a prospective observational study among 51 HIV-positive children in Rio De Janeiro after receiving seasonal influenza vaccine. 25 Some of our study participants experienced viral 'blips' post-vaccination. While not of sufficient magnitude to merit alteration in management, it may suggest mobilization of a latently infected CD4+ memory cell reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…Seroprotection was defined as the percentage of vaccines with an ABT Ն 1:40. Together with the main outcome, these secondary outcomes were used to evaluate immunogenicity (6). For a further outcome, we studied the changes in ABTs during 12 months using mixed linear regression models (see "Statistical analysis" below).…”
Section: Studymentioning
confidence: 99%
“…Similar results were previously reported, with no significant difference in the levels of HIV viral load between the moment of application of the influenza vaccine and 14-20 days and 60-90 days after its administration. 21 Several viruses could be identified during vaccination follow-up, highlighting that sensitive techniques are crucial to confirm influenza infection, considering the clinical similarities with other respiratory infections. In addition, our study also demonstrated that respiratory symptoms following influenza vaccination are generally caused by other respiratory viruses and are not necessarily indicative of vaccine failure.…”
Section: Hiv and Immunogenicity Of Influenza Vaccine 1001mentioning
confidence: 99%